Comparing the effectiveness of two surgical techniques for treating lower lid epiblepharon in children: a randomized controlled trial - Masaki Takeuchi; Nozomi Matsumura; Tomoko Ohno; Takeshi Fujita; Mizuki Asano; Nobuhisa Mizuki (Scientific Reports, 2023)
Abstract A multicenter randomized controlled trial was conducted to compare the effectiveness of incisional and nonincisional surgical techniques for treating lower lid epiblepharon in children. The study included 89 eyes from 50 children aged 3–15 years (mean, 7.5 ± 2.4 years) with moderate lower lid epiblepharon. Patients were randomly assigned to either incisional (modified Hotz procedure with lid margin splitting; 45 eyes of 25 patients) or nonincisional (44 eyes of 25 patients) surgery groups. Treatment outcomes and changes in astigmatism were evaluated 6 months after surgery. Incisional surgery provided a significantly higher percentage (77.8%) of well-corrected treatment results (P = 0.026; odds ratio, 2.88; 95% confidence interval, 1.07–8.22) than nonincisional surgery (55.4%). The mean change in astigmatism 6 months after surgery was − 0.24 ± 0.42 and − 0.01 ± 0.47 D in the incisional and nonincisional surgery groups, respectively. The improvement in astigmatism was significantly higher in the incisional surgery group than in the nonincisional surgery group (P = 0.008). The incisional surgical treatment for moderate epiblepharon in children resulted in a higher number of well-corrected patients, indicating an absence of both ciliary touch and superficial keratitis as well as statistically significant improvements in astigmatism correction.